Stewart Treves Syndrome - Pereira, Elisangela Samartin Pegas (An Bras Dermatol, 2015)
Stewart-Treves Syndrome is characterized by the presence of lymphangiosarcoma on limb extremities. Rare, it occurs in 0.5% of patients who have undergone radical mastectomy with axillary node dissection. The main cause is chronic lymphedema with endothelial and lymphatic differentiation, with no direct relationship to breast cancer. Seven years after a radical right-side mastectomy with lymph node dissection and adjuvant therapy, the patient developed a lesion on her right arm. The dermatological examination revealed an erythematous nodule with bleeding surface on chronic right forearm lymphedema. After the biopsy, a lymphangiosarcoma on chronic lymphedema was diagnosed. Infrequent, this syndrome is relevant because of its associated mortality. Early diagnosis is important to improve survival and reduce complications.